2010
DOI: 10.1103/physrevlett.104.173902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spatial Coherence on the Angular Distribution of Radiant Intensity Generated by Scattering on a Sphere

Abstract: In the analysis of light scattering on a sphere it is implicitly assumed that the incident field is spatially fully coherent. However, under usual circumstances the field is partially coherent. We generalize the partial waves expansion method to this situation and examine the influence of the degree of coherence of the incident field on the radiant intensity of the scattered field in the far zone. We show that when the coherence length of the incident field is comparable to, or is smaller than, the radius of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…(12) in the analysis of scattering of a Gaussian Schell-model beam by a sphere. In the analysis of scattering phenomena, one usually normalizes the scattered power by that of the incident field.…”
Section: Partially Coherent Incident Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…(12) in the analysis of scattering of a Gaussian Schell-model beam by a sphere. In the analysis of scattering phenomena, one usually normalizes the scattered power by that of the incident field.…”
Section: Partially Coherent Incident Fieldmentioning
confidence: 99%
“…Examples of partially coherent fields include those generated by multimode lasers and beams that have passed through a random medium, e.g., the turbulent atmosphere. Such more general situations have only recently begun to attract attention [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, numerous published articles exist predicting the polarization, coherence, and beam shape of partially coherent light after propagating through free space and random media [1][2][3][4][5][6][7][8][9][10] or scattering from deterministic and random objects/media. [11][12][13][14][15][16][17][18][19][20][21] Much work has also been performed exploiting coherence to control beam shape [22][23][24][25][26][27][28][29][30] and even as an encoding scheme for holography. 31 Excellent reviews and more in-depth discussions of these topics can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…As we will show, a rich variety of topological reactions occurs on propagation of these partially coherent, electromagnetic GSM beams. The observation that different cross sections of a GSM beam have different coherence properties, has profound implications for their use in scattering [37] and interference experiments [17].…”
Section: Introductionmentioning
confidence: 99%